First‐Principles Calculation of Bandgaps of Al1−xInxN Alloys and Short‐Period Al1−xInxN/Al1−yInyN Superlattices. Issue 4 (17th October 2019) - Kawamura, Takahiro; Fujita, Yuma; Hamaji, Yuya; Akiyama, Toru; Kangawa, Yoshihiro; Gorczyca, Izabela; Suski, Tadeusz; Wierzbowska, Małgorzata; Krukowski, Stanisław
Abstract : Bandgaps of AlInN alloys, short‐period InN/AlN superlattices (SLs), and short‐period AlInN alloy SLs are calculated using first‐principles calculations with the pseudopotential self‐interaction correction method. The dependence of these bandgaps on the composition and thickness of the SLs and the influence of strain are investigated. It is found that the bandgaps of the InN/AlN SLs depend on both the composition and thickness of the SLs. The maximum value of the bandgap equal to 2.56 eV is obtained for 1InN/4AlN SLs. The bandgaps of AlInN alloy SLs decrease with an increase in In content, and they cover the whole range between the values of AlN and InN. The bandgaps of InN/AlN SLs lattice‐matched to AlN are smaller than those of free‐standing InN/AlN SLs. Abstract : Bandgaps of AlInN alloys, short‐period InN/AlN superlattices (SLs), and short‐period AlInN alloy SLs are calculated using first‐principles calculations with the pseudopotential self‐interaction correction method. The bandgaps of the InN/AlN SLs depend on both the composition and thickness of the SLs.